2017
DOI: 10.1039/c7ra04723a
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-responsive methacrylamide polyampholytes

Abstract: The effective modulation of polymer cloud points in water is demonstrated through a series of charged, temperature-responsive methacrylamide-based polyampholytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…DMAPMAAm as a pH-dependent hydrophilic monomer contains a tertiary amino group with a pK a of 9.2, while PDMAPMAAm is reported to be completely protonated under physiological conditions with a pK a value of 8.8. 9,39 Ritter et al reported that the PDMAPMAAm hydrogel prepared via microwave-assisted synthesis was sensitive to both temperature and pH changes and exhibited an LCST at 35 1C and pH = 14 in water due to the protonation of its tertiary amine group. 28 Fig.…”
Section: Swelling Kinetics and Lcst Determination Of I-/t-pdmapmaam H...mentioning
confidence: 99%
“…DMAPMAAm as a pH-dependent hydrophilic monomer contains a tertiary amino group with a pK a of 9.2, while PDMAPMAAm is reported to be completely protonated under physiological conditions with a pK a value of 8.8. 9,39 Ritter et al reported that the PDMAPMAAm hydrogel prepared via microwave-assisted synthesis was sensitive to both temperature and pH changes and exhibited an LCST at 35 1C and pH = 14 in water due to the protonation of its tertiary amine group. 28 Fig.…”
Section: Swelling Kinetics and Lcst Determination Of I-/t-pdmapmaam H...mentioning
confidence: 99%
“…DMAPMAA has an alkylamine functional group, which provides water miscibility and acidity (p K a = 9.25). 35 Because of the acidity of TEA (p K a = 10.75), which is a representative organic base for water-based PAAS synthesis, the DMAPMAA has sufficient potential to be utilized as the organic base in the water-based synthesis of PAAS. In addition, DMAPMAA has a vinyl functional group that undergoes cross-linking via light-induced chemical reactions.…”
Section: Introductionmentioning
confidence: 99%